High-performance UHMWPE (Ultra High Molecular Weight Polyethylene) and slurry method preparation process thereof
By using a post-transition metal catalyst with 1,10-phenanthroline-5,6-dione as the framework, the problem of insufficient catalyst activity and thermal stability in the UHMWPE manufacturing process was solved, and the efficient preparation of bimodal UHMWPE at high temperature was achieved, which improved the processing performance of the product.
Patent Information
- Application Number
- CN202510044689.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-01-13
AI Technical Summary
There are problems of insufficient catalyst activity and thermal stability in the existing UHMWPE manufacturing process, which leads to a decrease in catalytic activity at high temperatures, limiting the application of UHMWPE in the high-end market.
Using a post-transition metal catalyst with 1,10-phenanthroline-5,6-dione as the framework, the preparation of bimodal UHMWPE is achieved by increasing the steric hindrance and rigid parent ring framework structure to improve catalytic activity and thermal stability.
The catalyst maintains high catalytic activity in a wide temperature range, especially with excellent thermal stability at high temperatures, and can prepare bimodal UHMWPE with a weight average molecular weight of 1.5 to 2 million and a PDI of 5 to 6, and has excellent product processing performance.
Smart Images

Figure CN119735721A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyethylene, and in particular to high-performance UHMWPE and a slurry preparation process thereof. Background Art
[0002] Ultra-High Molecular Weight Polyethylene (UHMWPE) has extremely high wear resistance and self-lubricating properties, making it very popular in industrial applications such as conveyors, gears and guide rails. Secondly, UHMWPE has excellent impact resistance, which makes it widely used in the field of national defense and military industry. In addition, UHMWPE also has good chemical resistance and low temperature resistance, which makes it widely used in aerospace, marine engineering, petrochemical, new energy materials and other fields. At present, the industrial structure has the problem of overcapacity in the middle and low-end and serious shortage of high-end products. At present, UHMWPE urgently needs to solve some key problems in its manufacturing process to promote UHMWPE to the high-end market. Polymerization reaction is the core of UHMWPE production, and the choice of catalyst plays a decisive role in the final performance of UHMWPE. Researchers have made a lot of efforts in this field and have made some progress. At present, ZN (Ziegler-Natta) catalyst and metallocene catalyst are the two main types of catalysts. ZN catalysts have become the mainstream choice due to their wide industrial applications, but their multi-active center characteristics lead to poor consistency in the microstructure of polyethylene products, making it difficult to meet the increasingly stringent requirements of the high-end market. To solve this problem, researchers have developed metallocene catalysts, which use a single active center to improve product consistency. However, the synthesis process of metallocene catalysts is relatively complicated, which to some extent limits their application in the polyethylene industry.
[0003] In view of the shortcomings of ZN catalysts and metallocene catalysts, researchers have further developed metal complex olefin catalysts with late transition metal atoms such as iron, cobalt, nickel, and palladium as the core. This type of catalyst is less sensitive to oxygen and moisture, and exhibits high activity in catalyzing olefin polymerization through structural regulation. Compared with ZN catalysts and metallocene catalysts, late transition metal catalysts have advantages such as higher stability, lower production cost, and the ability to produce new polyolefin products with polar groups. The synthesis of late transition metal catalysts is relatively simple, the yield is high, and the cost is much lower than that of ZN catalysts and metallocene catalysts, showing great industrial potential. However, the main obstacles to the industrial application of late transition metal catalysts are catalytic activity and thermal stability. Since ethylene polymerization is an exothermic reaction, most late transition metal catalysts are difficult to withstand high temperatures above 80°C, and the catalytic activity of late transition metal catalysts will also decrease at high temperatures. Chinese patent CN102775448B discloses a method for preparing late transition metal complexes and polyethylene, but it can only react at a lower temperature (≤60°C) and can only obtain low molecular weight polyethylene (molecular weight less than 2400).
[0004] α-Diimine-type late transition metal catalysts may be an effective strategy to solve the above problems. α-Diimine-type catalysts were discovered by Brookhart in 1995: the α-diimine Ni / Pd catalyst structure inhibits the β-H elimination chain transfer reaction in olefin polymerization by increasing steric hindrance, and high molecular weight polyethylene is obtained (Single Strand Targeted TriplexFormation: Parallel-Stranded DNA Hairpin Duplexes for Targeting PyrimidineStrands JACS., 1995, 117, 6416). The researchers improved the catalytic activity and thermal stability by constructing a rigid ring α-diimine structure with certain steric hindrance. Inspired by this, people mainly focus on improving the thermal stability by increasing the rigid structure and steric hindrance of the ligand. For example, Chinese patent CN110092744A discloses a highly thermally stable tert-butyl asymmetric diiminopyridine transition metal complex for preparing polyethylene wax, which has a single catalytic active center, high catalytic activity and good thermal stability. However, the amount of co-catalyst used is large (Al / Fe ≥ 1000), and it is used to prepare polyethylene wax with a low molecular weight.
[0005] In addition, due to the high molecular weight of UHMWPE, there are many difficulties in subsequent processing by extrusion, granulation, stretching and other processes. Bimodal polyethylene has both excellent mechanical properties and excellent processing properties. Its high molecular weight part is used to ensure its physical and mechanical strength, and the low molecular weight part plays a lubricating role in the resin, which can improve the processing performance of the product. At present, the processes for producing bimodal polyethylene mainly include: (1) melt mixing method, that is, producing resins of different molecular weights separately and then mixing them, which has the problems of high cost and uneven product quality. (2) staged reaction method, that is, by using a series of reactors to control different conditions to produce bimodal polyethylene with different molecular weights, it is flexible to operate and has a wide range of brand adjustment, but the cost is relatively high. (3) Directly obtain bimodal polyethylene through a one-stage reaction method, that is, directly obtain bimodal polyethylene by using a catalyst during polymerization, such as mixing different catalysts, using a catalytic system with multiple catalytic active points, etc. This method is a more ideal means.
[0006] Patent document CN104059184B uses a metallocene system to prepare bimodal polyethylene with adjustable molecular weight distribution, mainly by adjusting the addition concentration and addition time of the co-catalyst alkyl aluminum to regulate the composition of the product. Patent document CN105440184B uses a two-component composite catalytic system to prepare bimodal molecular weight distribution polyethylene by catalytic slurry polymerization of olefins in two series reactors. Patent document CN116640243A discloses a one-pot synthesis of bimodal polyethylene. During the polymerization process, two active centers are generated in situ by utilizing the two forms of retention and removal of H atoms to synthesize bimodal polyethylene. Patent document CN117986424B prepares branched bimodal polyethylene by using a dual-center metallocene catalyst, and the catalyst includes chromium metallocene, zirconium metallocene and modified silicon-based carrier. Patent document WO2023076208A1 discloses a method for preparing bimodal polyethylene by using a bimodal catalyst system and a trimming solution in a reactor, and the catalyst used is a metallocene compound or a non-metallocene catalyst. In summary, the new preparation process of high-performance UHMWPE still needs further research. Summary of the invention
[0007] The purpose of the present invention is to provide a high-performance UHMWPE and a slurry preparation process thereof in order to solve the above problems.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A high-performance UHMWPE slurry preparation process, using monomer ethylene as raw material, adding a catalyst to a solvent, carrying out a polymerization reaction at a temperature of 60-100°C and a pressure of 0.1-10MPa, and performing post-treatment after the reaction to obtain a UHMWPE product;
[0010] The catalyst is a late transition metal catalyst with 1,10-phenanthroline-5,6-dione as the skeleton as the main catalyst; The solvent is an inert organic solvent, including at least one of chain alkanes, cycloalkanes, and benzene aromatic derivatives having a boiling point not exceeding 120°C; The post-treatment includes: liquid-solid separation of the slurry after the reaction and drying the product.
[0011] Furthermore, the late transition metal catalyst is a nickel metal catalyst having a general structure shown in Formula C:
[0012]
[0013] Formula C
[0014] Wherein, X is chlorine or bromine;
[0015] R1-R6 are independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, C6-C 12 Aryl.
[0016] Preferably, at least one of R1-R3 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl; and / or at least one of R4-R6 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl.
[0017] More preferably, at least one of R1-R2 is selected from C1-C6 alkyl, C1-C6 alkoxy, C6-C 12 Phenyl; at least one of R3-R4 is selected from C1-C3 alkyl, C1-C3 alkoxy; and / or at least one of R5-R6 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl.
[0018] Preferably, at least one of R1 and R3 is a C1-C4 alkyl group or a phenyl group; and / or at least one of R4-R6 is a C1-C4 alkyl group.
[0019] The late transition metal catalyst used in the present invention has bimetallic active sites with different chemical environments and a rigid mother ring skeleton structure. When used for preparing UHMWPE by a slurry process, it maintains high catalytic activity and high thermal stability and can prepare bimodal UHMWPE.
[0020] As a preferred embodiment of the present invention, the late transition metal catalyst is selected from any one of the following formulae:
[0021]
[0022] Formula C1
[0023]
[0024] Formula C2
[0025]
[0026] Formula C4
[0027]
[0028] Formula C5
[0029]
[0030] Formula C6
[0031]
[0032] Formula C7
[0033]
[0034] Formula C8
[0035]
[0036] Formula C9
[0037] Furthermore, the late transition metal catalyst is a coordination compound formed by a diimine ligand having a structure as shown in Formula L and a nickel salt, and the specific reaction formula is as follows:
[0038]
[0039] Formula L Formula C.
[0040] Specifically, the following method can be adopted: the diimine ligand and the nickel salt are dissolved in an anhydrous aprotic organic solvent at a molar ratio of 1:3-4, and the mixture is reacted in an anhydrous and oxygen-free environment to obtain the product.
[0041] Furthermore, the nickel metal catalyst is prepared by the following method: dissolving the prepared ligand L and nickel salt in an anhydrous aprotic organic solvent (e.g., acetonitrile, toluene) at a molar ratio of 1:3-4, controlling an anhydrous and oxygen-free environment, and reacting at a reaction temperature of 40-100° C. for 12-36 hours. After the reaction is completed, filter, wash with distilled water 2-3 times, and dry the sample in a vacuum drying oven.
[0042] Furthermore, the diimine ligand having the general structure shown in Formula L is:
[0043]
[0044] Formula L
[0045] Wherein, R1-R6 can be the same or different groups, and R1-R6 are independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, C6-C 12 Aryl.
[0046] The C1-C6 alkyl group includes a linear or branched alkyl group, such as but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, pentyl or hexyl, preferably methyl, isopropyl or tert-butyl.
[0047] The C1-C6 alkoxy group includes methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, pentyloxy or hexyloxy.
[0048] The C6-C 12 Aryl is a monovalent aromatic carbocyclic ring system having at least one aromatic ring or multiple condensed rings in which at least one ring is aromatic, for example, may be selected from phenyl, naphthyl or biphenyl.
[0049] As a preferred technical solution, at least one of R1-R2 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl; at least one of R3-R4 is selected from C1-C3 alkyl, C1-C3 alkoxy; and / or at least one of R5-R6 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl, and the rest are H.
[0050] As a preferred technical solution, at least one of R1 and R3 is a C1-C4 alkyl group or a phenyl group, for example, selected from a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a tert-butyl group, etc. or a phenyl group; and / or at least one of R4-R6 is a C1-C4 alkyl group, for example, selected from a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a tert-butyl group, etc., and the rest are H.
[0051] As a preferred embodiment of the present invention, the diimine ligand is selected from any one of the following diimine ligand compounds:
[0052]
[0053] Formula L1
[0054]
[0055] Formula L2
[0056]
[0057] Formula L4
[0058]
[0059] Formula L5
[0060]
[0061] Formula L6
[0062]
[0063] Formula L7
[0064]
[0065] Formula L8
[0066]
[0067] Formula L9
[0068] The diimine ligand of the structure shown in Formula L of the present invention has a phenanthroline skeleton structure. On the one hand, the 1,10-phenanthroline skeleton has a certain rigidity and can provide a steric effect to prevent the late transition metal catalyst from being deactivated at high temperature; on the other hand, the 1,10-phenanthroline skeleton has two N atoms, and the different electronegativity of the N atom and the C atom helps to improve the electronic effect of the catalyst; in addition, the 1,10-phenanthroline-5,6-dione skeleton structure can form two active sites after metal coordination after reacting with amines, and the chemical environments between the two active sites are completely different, so that bimodal ultra-high molecular weight polyethylene can be produced.
[0069] The preparation method of the above-mentioned diimine ligand is to use a 1,10-phenanthroline-5,6-dione derivative of the general structure shown in Formula I and an aniline derivative of the general structure shown in Formula II as raw materials to prepare the diimine ligand through acid catalysis. The specific reaction formula is as follows:
[0070]
[0071] Formula I Formula II Formula L
[0072] In the 1,10-phenanthroline-5,6-dione derivative of the general structure shown in Formula I, R1-R2 can be the same or different groups, independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, aromatic naphthyl, aromatic biphenyl, etc.; R3 can be the same or different groups, independently selected from H, C1-C3, C1-C3 alkoxy, etc. Preferably, a 1,10-phenanthroline derivative with an electron-donating effect is used as the ortho-dicarbonyl raw material, and it is further preferred to use 1,10-phenanthroline with electron-donating effect groups on R1 and R3 as the ortho-dicarbonyl raw material. It is further preferred that 1,10-phenanthroline with certain sterically hindered electron-donating groups on R1 and R3 is used as the ortho-dicarbonyl raw material. It is further preferred that 1,10-phenanthroline with R1 being methyl, isopropyl, phenyl and R3 being methyl is used as the ortho-dicarbonyl raw material.
[0073] In an embodiment of the present invention, the 1,10-phenanthroline-5,6-dione derivative can be selected from 1,10-phenanthroline-5,6-dione, 2,9-dimethyl-1,10-phenanthroline-5,6-dione, 2,9-diphenyl-1,10-phenanthroline-5,6-dione, 2,9-diisopropyl-1,10-phenanthroline-5,6-dione, 4,7-dimethyl-1,10-phenanthroline-5,6-dione, 2,9-diphenyl-1,10-phenanthroline-5,6-dione, 2,9-diphenyl-1,10-phenanthroline-5,6-dione, 2,9-diphenyl-1,10-phenanthroline-5,6-dione, 2,9-diphenyl-1,10-phenanthroline-5,6-dione, and the like.
[0074] The aniline derivative of the general structure shown in Formula II has a primary amine as the main skeleton, and R4 can be the same or different H, C1-C6 alkyl, C1-C6 alkoxy, etc. Preferably, a primary amine with an electron-donating effect is used as the amine raw material, and more preferably, an electron-donating group primary amine with a certain steric hindrance effect is used as the amine raw material. Methylamine, aniline, 3,5-dimethylaniline, and p-methylaniline are further preferred as the amine raw materials.
[0075] In an embodiment of the present invention, the aniline derivative is selected from aniline, o-methylaniline, 3,5-dimethylaniline, p-methylaniline and the like.
[0076] As a preferred technical solution, the preparation method of the diimine ligand of the present invention comprises the following steps: 1,10-phenanthroline-5,6-dione derivative and aniline derivative are dissolved in a non-protonic polar organic solvent at a molar ratio of 1:2 to 2.5, and then a non-oxidizing organic strong acid is used as a catalyst (catalytic level) to react at 40 to 150° C. After the reaction, the solvent is removed from the mixture and purified to obtain the diimine ligand.
[0077] Preferably, the organic aprotic polar solvent can be a commonly used solvent in the art, such as benzene, toluene, etc. The non-oxidizing organic strong acid can be a commonly used solvent organic strong acid substance in the art, such as p-toluenesulfonic acid. The reaction temperature is preferably 60-100° C., and the reaction time is generally between 12-36 hours. The solvent can be removed by conventional methods in the art, such as rotary evaporation. The product can be purified by conventional methods in the art, such as recrystallization and column chromatography.
[0078] The inventors have found that the late transition metal catalyst using the novel structure unexpectedly has high catalytic activity in a wide temperature range, especially excellent high temperature stability. For example, when the reaction temperature is 80°C, the catalyst has a high stability of 7.88×10 6The specific mechanism is not very clear yet. The possible reason is speculated to be: the late transition metal catalyst with 1,10-phenanthroline-5,6-dione as the skeleton has higher rigidity and better electronic effect than the traditional 1,2-diketone structure, which prevents the late transition metal catalyst from being deactivated at high temperature. The 1,10-phenanthroline skeleton is different from phenanthrene. It has two N atoms in its ring. The different electronegativity of N atoms and C atoms also helps to improve the electronic effect of the catalyst; in addition, the 1,10-phenanthroline-5,6-dione skeleton structure can form two active sites after metal coordination after reaction with amines, and the chemical environment between the two active sites is completely different, which can produce bimodal ultra-high molecular weight polyethylene.
[0079] The late transition metal catalyst, under the action of a co-catalyst, can obtain bimodal ultra-high molecular weight polyethylene at a relatively low pressure and with high catalytic activity.
[0080] Furthermore, the solvent is preferably a benzene aromatic derivative or alkane that is liquid at room temperature, has low viscosity, a boiling point not exceeding 110° C., and has low solubility in ultra-high molecular weight polyethylene, such as toluene, xylene, chlorobenzene, hexane, etc.
[0081] Furthermore, the catalyst also includes a co-catalyst, and the co-catalyst is selected from at least one of alkylaluminoxane, alkylaluminum, and aromatic boron. Further, the selected co-catalyst is mainly alkylaluminoxane, and more preferably methylaluminoxane, modified methylaluminoxane, and isobutylaluminoxane are used as co-catalysts. The molar ratio of the late transition metal catalyst to the co-catalyst is 1:200~500.
[0082] Furthermore, when producing ultra-high molecular weight polyethylene, the polymerization temperature is 70-90°C, and the pressure in the reactor is controlled by ethylene gas, and the pressure is 0.1-2Mpa, preferably 0.1-1Mpa.
[0083] Compared with the prior art, the present invention has the following innovative features:
[0084] The present invention uses a novel structure of a diimine post-transition metal catalyst as a main catalyst when preparing UHMWPE by a slurry method. The catalyst has a bimetallic active site with different chemical environments and a rigid mother ring skeleton structure. The catalyst uses 1,10-phenanthroline-5,6-dione as a skeleton. The phenanthrene ring structure in the structure has a certain rigidity and can improve the catalytic activity and thermal stability. In addition, there are two pyridine rings in 1,10-phenanthroline-5,6-dione, and the pyridine ring and the benzene ring have significantly different electronic effects. The lone pair of electrons on the N atom can be conjugated with the benzene ring and the diimine structure to further optimize the electronic structure of the catalyst, and can produce two metal active centers with completely different chemical environments. The bimodal UHMWPE can be prepared by a one-step reaction, and the product has good processing performance. The obtained UHMWPE has a weight average molecular weight distribution of 1.5 to 2 million, a PDI of 5 to 6, and excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] Figure 1 The molecular weight distribution graph of polyethylene sample E8 is shown. DETAILED DESCRIPTION
[0086] The present invention is described in detail below. All matters not described in detail in the present invention are technical solutions already disclosed in the art.
[0087] The specific sources of the main reagents used in each embodiment are as follows:
[0088] 1,10-Phenanthroline-5,6-dione (CAS: 27318-90-7, Sigma-Aldrich)
[0089] 2,9-Dimethyl-1,10-phenanthroline-5,6-dione (CAS: 102331-54-4, Henan Weitixi Chemical)
[0090] 2,9-Diphenyl-1,10-phenanthroline-5,6-dione (CAS: 1654020-68-4, Henan Lien Chemical)
[0091] 2,9-Diisopropyl-1,10-phenanthroline-5,6-dione (CAS: 1243254-92-3, Henan Lien Chemical)
[0092] 4,7-Dimethyl-1,10-phenanthroline (CAS: 3248-05-3, Leyan Reagent)
[0093] 4,7-Dimethyl-1,10-phenanthroline-5,6-dione (CAS: 1713236-32-8, obtained by synthesis)
[0094] 2,3-Butanedione (CAS: 431-03-8, Sigma-Aldrich)
[0095] 2,6-Diacetylpyridine (CAS: 1129-30-2, Sigma-Aldrich)
[0096] Salicylaldehyde (CAS: 90-02-8, Sigma-Aldrich)
[0097] Methylaluminoxane (CAS: 120144-90-3, Jiuding Chemical)
[0098] High purity ethylene (CAS: 74-85-1, Shanghai Liquid Gas)
[0099] Aniline (CAS: 62-53-3, Sigma-Aldrich)
[0100] o-Toluidine (CAS: 95-53-4, Sigma-Aldrich)
[0101] 3,5-Dimethylaniline (CAS: 108-69-0, Sigma-Aldrich)
[0102] p-Toluidine (CAS: 106-49-0, Sigma-Alrich)
[0103] p-Bromoaniline (CAS: 106-40-1, Sigma-Aldrich)
[0104] p-Toluenesulfonic acid (CAS: 6192-52-5, Sigma-Aldrich)
[0105] Acetic acid (CAS: 64-19-7, Sigma-Aldrich)
[0106] Ethanol (CAS: 64-17-5, Sigma-Aldrich)
[0107] Dichloromethane (CAS: 75-09-2, Sigma-Aldrich)
[0108] Benzene (CAS: 71-43-2, Sigma-Aldrich)
[0109] Toluene (CAS: 108-88-3, Sigma-Aldrich)
[0110] Concentrated sulfuric acid 98% (CAS: 76664-93-9, Sigma-Aldrich)
[0111] Nitric acid (CAS: 7697-37-2, Sigma-Aldrich)
[0112] Sodium hydroxide (CAS:1310-73-2, Sigma-Aldrich)
[0113] Hydrochloric acid (CAS: 7647-01-0, Sigma-Aldrich)
[0114] Acetonitrile (CAS: 75-05-8, Sigma-Aldrich)
[0115] Methanol (CAS: 67-56-1, Sigma-Aldrich)
[0116] Unless otherwise specified, all solvents used in the examples must be anhydrous.
[0117] Preliminary Example 1
[0118] Catalyst sample 1 was prepared as follows:
[0119] (1) The specific synthesis method of ligand L1 is as follows:
[0120]
[0121] 2.10 g of 1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of benzene was added to dissolve it, followed by 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 65°C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by vacuum distillation, and the product was recrystallized and purified with ethanol, and dried to obtain ligand L1, with a final yield of 90%. ( 1 H 300MHz, DMSO): 9.12-7.11 (m, 16H, Ar-H). C 24 H 16 N4: Elemental analysis calculated values (%): C, 79.98; H, 4.47; N, 15.55. Experimental determination values (%): C, 80.11; H, 4.55; N, 15.41.
[0122] (2) Preparation of catalyst sample 1: The obtained ligand L1 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L1 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to be 55°C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 1.
[0123] Preliminary Example 2
[0124] Catalyst sample 2 was prepared as follows:
[0125] (1) The specific synthesis method of ligand L2 is as follows:
[0126]
[0127] 2.38 g (10 mmol) of 2,9-dimethyl-1,10-phenanthroline-5,6-dione was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100°C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L2, with a final yield of 85% ( 1 H300MHz, DMSO): 8.84-7.30 (m, 14H, Ar-H); 2.95 (d, 6H,-CH3). C 26 H 20 N4: Elemental analysis calculated value (%): C, 80.39; H, 5.19; N, 14.42. Experimental determination value (%): C, 80.66; H, 5.29; N, 14.07.
[0128] (2) Preparation of catalyst sample 2: The obtained ligand L2 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L2 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 2.
[0129] Preparatory Example 3
[0130] Catalyst sample 3 was prepared as follows:
[0131] (1) The specific synthesis method of ligand L3 is as follows:
[0132]
[0133] 3.68 g of 2,9-dibromo-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L3, with a final yield of 71% ( 1 H300MHz, DMSO): 9.14-7.22 (m, 14H, Ar-H). C 24 H 14 N4Br2: Calculated values by elemental analysis (%): C, 55.63; H, 2.72; N, 10.81; Br, 30.84. Experimen-tally determined values (%): C, 55.77; H, 2.85; N, 10.71; Br, 30.73.
[0134] (2) Preparation of catalyst sample 3: The obtained ligand L3 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L3 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to be 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 3.
[0135] Preliminary Example 4
[0136] Catalyst sample 4 was prepared as follows:
[0137] (1) The specific synthesis method of ligand L4 is as follows:
[0138]
[0139] 3.62 g of 2,9-diphenyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L4, with a final yield of 88% ( 1 H300MHz, DMSO): 9.33-7.42 (m, 24H, Ar-H). C 36 H24 N4: Elemental analysis calculated values (%): C, 84.35; H, 4.72; N, 10.92. Experimental determination values (%): C, 84.69; H, 4.82; N, 10.57.
[0140] (2) Preparation of catalyst sample 4: The obtained ligand L4 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L4 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to be 55°C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 4.
[0141] Preliminary Example 5
[0142] Catalyst sample 5 was prepared as follows:
[0143] (1) The specific synthesis method of ligand L5 is as follows:
[0144]
[0145] 2.94 g of 2,9-diisopropyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L5, with a final yield of 91% ( 1 H300MHz, DMSO): 8.79-7.52 (m, 14H, Ar-H); 3.95-1.77 (m, 14H, -CH(CH3)2). C 30 H 28 N4: Elemental analysis calculated value (%): C, 80.39; H, 6.35; N, 12.60. Experimental determination value (%): C, 80.87; H, 6.43; N, 12.07.
[0146] (2) Preparation of catalyst sample 5: The obtained ligand L5 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L5 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 5.
[0147] Preliminary Example 6
[0148] Catalyst sample 6 was prepared as follows:
[0149] (1) The specific synthesis method of ligand L6 is as follows:
[0150]
[0151]
[0152] First, synthesize 4,7-dimethyl-1,10-phenanthroline-5,6-dione: 1.35 g (6.5 mmol) of 4,7-dimethyl-1,10-phenanthroline and potassium bromide (7.5 g) were mixed, sulfuric acid (30 ml) was added dropwise at 0°C within 15 minutes, and then nitric acid (15 ml, dripped within 15 minutes) was added to the reaction mixture. The resulting mixture was heated at 80°C for 4 hours, and the solution was cooled to 0°C after the reaction. The cold acidic mixture was poured onto ice. A 5% NaOH solution was added to the reaction mixture under vigorous stirring to adjust the pH to 3. The mixture was extracted with dichloromethane (3×300 ml), the organic phase was dried with MgSO4, the solvent was evaporated, and the resulting solid was vacuum dried for standby use.
[0153] 2.38 g of 4,7-dimethyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it. Then, 2.14 g of aniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol) were added. The three-necked flask was heated to 100 °C and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L6. The final yield was 75% ( 1 H300MHz, DMSO): 9.14-7.25 (m, 14H, Ar-H); 3.12-2.56 (m, 6H,-CH3). C 26 H 20N4: Calculated values by elemental analysis (%): C, 80.39; H, 5.19; N, 14.42. Experimen-tally determined values (%): C, 80.42; H, 5.21; N, 14.37.
[0154] (2) Preparation of catalyst sample 6: The obtained ligand L6 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L6 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 6.
[0155] Preparatory Example 7
[0156] Catalyst sample 7 was prepared as follows:
[0157] (1) The specific synthesis method of ligand L7 is as follows:
[0158]
[0159] 3.62 g of 2,9-diphenyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it. Then, 2.46 g of o-methylaniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol) were added. The three-necked flask was heated to 100 °C and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L7 with a final yield of 68% ( 1 H 300MHz, DMSO): 8.52-7.49 (m, 22H, Ar-H); 2.50 (s, 6H,-CH3). C 38 H 28 N4: Elemental analysis calculated value (%): C, 84.42; H, 5.22; N, 10.36. Experimental determination value (%): C, 84.45; H, 5.26; N, 10.33.
[0160] (2) Preparation of catalyst sample 7: The obtained ligand L7 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L7 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 7.
[0161] Preparatory Example 8
[0162] Catalyst sample 8 was prepared as follows:
[0163] (1) The specific synthesis method of ligand L8 is as follows:
[0164]
[0165] 3.62 g of 2,9-diphenyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.78 g of 3,5-dimethylaniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L8, with a final yield of 68% ( 1 H 300MHz, DMSO): 9.05-7.16 (m, 20H, Ar-H); 2.82-1.80 (m, 12H,-CH3). C 40 H 32 N4: Elemental analysis calculated values (%): C, 84.48; H, 5.67; N, 9.85. Experimental determination values (%): C, 84.51; H, 5.72; N, 9.77.
[0166] (2) Preparation of catalyst sample 8: The obtained ligand L8 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L8 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 8.
[0167] Preparatory Example 9
[0168] Catalyst sample 9 was prepared as follows:
[0169] (1) The specific synthesis method of ligand L9 is as follows:
[0170]
[0171] 3.62 g of 2,9-diphenyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 2.46 g of p-methylaniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L9 with a final yield of 84% ( 1 H300MHz, DMSO): 8.99-7.58 (m, 22H, Ar-H); 2.91-1.77 (m, 6H,-CH3). C 38 H 28 N4: Elemental analysis calculated value (%): C, 84.42; H, 5.22; N, 10.36. Experimental determination value (%): C, 84.55; H, 5.33; N, 10.30.
[0172] (2) Preparation of catalyst sample 9: The obtained ligand L9 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L9 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to be 55 °C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, washed with dry n-hexane for several times, and dried to obtain catalyst sample 9.
[0173] Preparatory Example 10
[0174] Catalyst sample 10 was prepared as follows:
[0175] (1) The specific synthesis method of ligand L10 is as follows:
[0176]
[0177] 3.62 g of 2,9-diphenyl-1,10-phenanthroline-5,6-dione (10 mmol) was added to a 250 ml three-necked flask, and about 100 ml of anhydrous acetic acid was added to dissolve it, followed by 3.95 g of p-bromoaniline (23 mmol) and 7 μL of p-toluenesulfonic acid (about 50 μmol). The three-necked flask was heated to 100 °C, and a condenser with a water separator was used to react for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the product was recrystallized and purified using ethanol to obtain ligand L10, with a final yield of 73% ( 1 H 300MHz, DMSO): 9.23-7.67 (m, 22H, Ar-H). C 36H 22 N4Br2: Elemental analysis calculated value (%): C, 64.50; H, 3.31; N, 8.36; Br, 23.84. Experimental determination value (%): C, 64.62; H, 3.33; N, 8.44; Br, 23.79.
[0178] (2) Preparation of catalyst sample 10: The obtained ligand L10 was coordinated with NiC12. The specific steps were as follows: under anhydrous and oxygen-free conditions, about 100 ml of ultra-dry acetonitrile was added to a three-necked flask, and the ligand L10 (8.4 mmol) and anhydrous NiC12 (4 mmol) were added. The reaction temperature was controlled to be 55°C and the reaction time was 24 hours. After the reaction was completed, it was cooled to room temperature, concentrated by reduced evaporation, the solvent was filtered out, and the mixture was washed several times with dry n-hexane and dried to obtain catalyst sample 10.
[0179] The catalysts and raw materials of Preparatory Examples 1 to 10 are detailed in Table 1.
[0180] Table 1 Catalysts and raw materials of the preparation examples
[0181]
[0182] The present invention also provides the following comparative examples.
[0183] Comparative Example 1
[0184] Catalyst sample a was prepared according to the following steps.
[0185] (1) Synthesis of pyridine diimine ligand:
[0186]
[0187] 0.82 g of 2,6-diacetylpyridine (5 mmol) and 1.65 g of 4-amino-3,5-dimethylphenol (12 mmol) were dissolved in 150 ml of methanol, 1 ml of formic acid was added and refluxed at 80 °C for 12 hours. After the reaction was completed, the solvent was evaporated and concentrated and recrystallized by adding n-hexane to obtain ligand L.
[0188] (2) Preparation of catalyst sample a:
[0189]
[0190] Under nitrogen, 1 mmol of ligand L was dissolved in 30 ml of THF and reacted for 1 hour. FeCl2 was then added and reacted for 6 hours. THF was removed by rotary evaporation to obtain catalyst a. The final yield was 85%. ( 1H 300MHz, DMSO): 9.27 (s, 2H, -OH); 8.72-7.04 (m, 7H, -Ar-H); 2.68-2.11 (m, 18H, -CH3). C 25 H 27 N3O2: Elemental analysis calculated value (%): C, 74.79; H, 6.78; N, 10.47; O, 7.97. Experimental determination value (%): C, 74.78; H, 6.73; N, 10.54; O, 8.02.
[0191] Comparative Example 2
[0192] Catalyst sample b: Commercially available metallocene catalyst titanocene dichloride (CAS: 1271-19-8), the structural formula of which is:
[0193]
[0194] Example
[0195] The above catalysts were used as main catalysts to prepare polyethylene through slurry polymerization process and the catalyst performance was tested. The specific steps are as follows:
[0196] A 250 ml stainless steel reactor (with a cooling jacket) was heated at 150 ° C for about 30 min in vacuum, then cooled to ambient temperature, and the reactor was pressurized to 2 atm with ethylene. After venting, it was pressurized again with ethylene. This was repeated three times to ensure that the reactor was filled with ethylene atmosphere. The cocatalyst MAO (0.5 mmol) was dissolved in about 100 ml of dry hexane and injected into the reactor. It was stirred continuously for 5 min under 1.2 atm ethylene pressure. Finally, 50 ml of catalyst hexane dilution (containing about 2 μmol of catalyst) was added to the reactor with a syringe and stirred evenly. Gaseous ethylene was continuously added during the entire reaction process, and the ethylene pressure in the reactor was maintained at 9~10 atm. The reaction temperature was controlled at 60~100 ° C during the polymerization process. The polymerization process was completed after the reaction lasted for 2 h, and then post-treatment was performed. Acidic methanol (mass ratio 95:5 ethanol / hydrochloric acid) was added to deactivate the catalyst. The resulting precipitated polymer was collected, separated and rotary evaporated, and dried to a fixed weight in a vacuum at 40 ° C to obtain a polyethylene sample, which was weighed and tested.
[0197] The activity of the catalyst was calculated based on the yield of the polyethylene sample, in g polyethylene / (mol catalyst×h). Table 2 lists the catalytic activity of each catalyst at different temperatures.
[0198] Table 2 Catalytic activity of different catalysts at different temperatures (unit: 10 6 g PE / mol cat h)
[0199]
[0200] Note: “--” means not performed.
[0201] As shown in Table 2, sample a is a catalyst obtained from pyridine diimine ligand (without 1,10-phenanthroline-5,6-dione skeleton structure), with poor thermal stability, and its catalytic activity is significantly weakened above 80°C. Sample b metallocene catalyst dichlorotitacenene has good catalytic activity at 70-80°C, but after 100°C, its catalytic activity is significantly weakened. Compared with the comparative example, except for samples 3 and 10 with halogen as substituents, other catalyst samples show excellent thermal stability (especially when donating electrons with a certain steric hindrance effect), and maintain excellent ethylene catalytic activity at temperatures of 80-100°C, indicating that the late transition metal catalyst obtained using 1,10-phenanthroline-5,6-dione as the diimine structure skeleton has high catalytic activity and thermal stability. For example, the catalytic activity of sample 8 at 90°C can reach 7.88×10 6 gPE / g cat h, catalytic activity at 100℃ is 4.57×10 6 gPE / g cat h.
[0202]
Polyethylene sample performance test
[0203] Some of the polyethylene samples obtained above were selected for molecular weight determination: the weight average molecular weight (Mw) and number average molecular weight (Mn) were determined by gel permeation chromatography according to GB / T 27843-2011 "Determination of low molecular weight component content of chemical polymers by gel permeation chromatography (GPC)"; the molecular weight distribution index (PDI) of polyethylene was determined by the ratio of the measured weight average molecular weight and number average molecular weight; the peak distribution was determined based on the GPC molecular weight distribution curve. See Table 3 for specific test results. Figure 1 The molecular weight distribution profile of polyethylene sample E8 is exemplified.
[0204] Table 3 Test results of polyethylene samples
[0205]
[0206] As shown in Table 3, the present invention prepares bimodal ultra-high molecular weight polyethylene. Except for polyethylene samples E3 and E10 prepared by catalyst samples 3 and 10 with halogen as substituents, the weight average molecular weight of the polyethylene of the present invention is distributed in 1.5-2 million, and the PDI is 5-6, which are all bimodal polyethylenes, and have better processing performance. Comparative Example 1 only obtains a low molecular weight polyethylene product and is a unimodal polyethylene, and Comparative Example 2 prepares a unimodal polyethylene.
[0207] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A high-performance UHMWPE slurry preparation process, characterized in that: Using monomer ethylene as raw material, adding a catalyst into the solvent, carrying out polymerization reaction at a temperature of 60-100°C and a pressure of 0.1-10MPa, and performing post-treatment after the polymerization reaction to obtain UHMWPE products; The catalyst is a late transition metal catalyst with 1,10-phenanthroline-5,6-dione as the skeleton as the main catalyst; The solvent is an inert organic solvent, including at least one of chain alkanes, cycloalkanes, and benzene aromatic derivatives having a boiling point not exceeding 120°C; The post-treatment includes: liquid-solid separation of the slurry after the reaction and drying the product.
2. A high performance UHMWPE slurry preparation process according to claim 1, characterized in that: The late transition metal catalyst is a nickel metal catalyst having a general structure shown in Formula C: , Wherein, X is chlorine or bromine; R1-R6 are independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, C6-C 12 Aryl.
3. A high performance UHMWPE slurry preparation process according to claim 2, characterized in that: At least one of R1-R3 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl; And / or, at least one of R4-R6 is selected from C1-C6 alkyl, C1-C6 alkoxy or phenyl.
4. A high performance UHMWPE slurry preparation process according to claim 2, characterized in that: At least one of R1 and R3 is a C1-C4 alkyl group or a phenyl group; And / or, at least one of R4-R6 is a C1-C4 alkyl group.
5. A high performance UHMWPE slurry preparation process according to any one of claims 2 to 4, characterized in that: The late transition metal catalyst is a coordination compound formed by a diimine ligand having a structure as shown in Formula L and a nickel salt, and the specific reaction formula is as follows: 。 6. A high performance UHMWPE slurry preparation process according to claim 1, characterized in that: The catalyst further comprises a co-catalyst, and the co-catalyst is selected from at least one of alkylaluminoxane, alkylaluminum, and aromatic boron; The molar ratio of the late transition metal catalyst to the co-catalyst is 1:200-500.
7. A high performance UHMWPE slurry preparation process according to claim 1, characterized in that: The polymerization temperature is 70-90°C, and the pressure in the reactor is controlled by ethylene gas at a pressure of 0.1-2Mpa.
8. A high performance UHMWPE slurry preparation process according to claim 7, characterized in that: The pressure is 0.1-1Mpa.
9. A UHMWPE obtained according to the preparation process according to any one of claims 1 to 8, characterized in that: The UHMWPE is a bimodal polyethylene with a weight average molecular weight distribution of 1.5 to 2 million and a PDI of 5 to 6.
Citation Information
Patent Citations
Post-transition metal complex, preparation method thereof and polyethylene preparation method
CN102775448B
A method for preparing bimodal polyethylene with tunable molecular weight distribution using a metallocene system
CN104059184B
A method for preparing high-density polyethylene with a bimodal molecular weight distribution
CN105440184B
A class of high thermal stability coordination compounds containing tert-butyl asymmetric diimine pyridine, preparation method and applications thereof
CN110092744A
Dual-site metallocene catalyst and its application in preparing branched bimodal polyethylene
CN117986424B
Cited By
High-performance uhmwpe and preparation process therefor by means of slurry method
WO2026149039A1